Effects of camber on the ergonomics of propulsion in wheelchair athletes - Mason, B.; van der Woude, L.; de Groot, S.; Goosey-Tolfrey, V. L. (Medicine & Science in Sports & Exercise, 2011)
Purpose: To examine the effects of rear-wheel camber on the physiological and biomechanical responses during manual wheelchair propulsion in highly trained wheelchair athletes.